Factors Influencing Different Stages of Growth in First-Generation Boer Crossbred Goats - Sapkota, Saroj; Poudel, Jib Raj; Sharma, Mohan Prasad; Amatya Gorkhali, Neena; Bhattarai, Nirajan (Journal of Agriculture and Forestry University, 2025)
This study aimed to evaluate the growth performance of first-generation Boer crossbred kids, focusing on the effect of non-genetic factors like location, breed, production system, herd size, sex, parity, dam size, and birth type. The research was carried out at two municipalities of Surkhet district namely Birendranagar and Lekbesi. Data were gathered from 901 kids and 446 does raised in a pasture and stall-feeding system. The data were analyzed using the Mixed Model Least-square and Maximum Likelihood Computer Program PC-2 statistical package, and the means were compared using Duncan’s Multiple Range Test (DMRT). In this study, the least means square live birth weight, pre-weaning weight, weaning weight, post-weaning weight, weight at 6 months and weight at 12 months were 3.30±0.06 kg, 12.45±0.26 kg, 19.23±0.36 kg, 24.17±0.53 kg, 27.96±0.98 kg, and 34.68±1.53 kg respectively. The results revealed that breed, birth type, sex, location, herd size, and production system are significant factors influencing growth variations in goats. These insights can guide goat farmers in planning effective strategies for extensive and intensive crossbred goat production and farming.